The Effect of Deferred Tax and Tax to Book Ratio on Company Financial Performance - Dita Damayanti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Company performance is a description of a company whether the company has carried out procedures in accordance with applicable regulations. One tool that can be used to measure company performance is financial ratios. BenefitFinancial ratio analysis in looking at a company will provide an overview of the company's condition and can be used as a predictive tool for the company in the future. The financial ratio indicator used is the profitability ratio, one of which is return on assets. There are several components that can affect the company's performance improvement, namely deferred taxes. Deferred tax affects company performance. The higher the deferred tax expense, the higher the company performance, while the tax to book ratio affects company performance.This study aims to determine the effect of deferred tax and tax to book ratio on the financial performance of manufacturing companies in the food and beverages sub-sector which are listed on the Indonesia Stock Exchange. The population of this study is the food and beverages sub-sector manufacturing companies listed on the Indonesia Stock Exchange as many as 26 companies. Based on the sampling technique using purposive sampling from 26 companies, 12 companies were obtained that matched the predetermined criteria. The type of research used is quantitative data in the form of secondary data obtained from annual financial reports for 5 years of the object of observation. The data analysis technique used is classical assumption testing analysis including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test.